You cannot hide your telephone lies: Providing a model statement as an aid to detect deception in insurance telephone calls - Leal, Sharon (Legal and criminological psychology, 2015)
Deception research regarding insurance claims is rare but relevant given the financial loss in terms of fraud. In Study 1, a field study in a large multinational insurance fraud detection company, truth telling mock claimants (N = 19) and lying mock claimants (N = 21) were interviewed by insurance company telephone operators. These operators classified correctly only 50% of these truthful and lying claimants, but their task was particularly challenging: Claimants said little, and truthful and deceptive statements did not differ in quality (measured with Criteria-Based Content Analysis [CBCA]) or plausibility. In Study 2, a laboratory experiment, participants in the experimental condition (N = 43) were exposed to an audiotaped truthful and detailed account of an event that was unrelated to insurance claims (a day at the motor races). The number of words, quality of the statement (measured with CBCA), and plausibility of the participants' accounts were compared with participants who were not given a model statement (N = 40). The participants who had listened to the model statement provided longer statements than control participants, truth tellers obtained higher CBCA scores than liars, and only in the model statement condition did truth tellers sound more plausible than liars. Providing participants with a model statement is thus an innovative and successful tool to elicit cues to deception. Providing such a model has the potential to enhance performance in insurance call interviews, and, as we argue, in many other interview settings.